Low T3 syndrome is a prognostic marker of poor outcomes in secondary hemophagocytic lymphohistiocytosis. Issue 12 (14th October 2020) - Yin, Guang-Li; Huang, Jia-Yu; Tian, Tian; Duan, Li-Min; Xu, Ji; Qiu, Hong-Xia
Abstract: This study aimed to examine the association between low T3 syndrome and overall survival (OS) in patients with secondary hemophagocytic lymphohistiocytosis (sHLH). The study consisted of 111 consecutive patients hospitalized due to newly diagnosed sHLH with detailed thyroid hormone profiles on admission. Low T3 syndrome was found in 75.7% of the studied sHLH population. After a median follow-up of 83 (interquartile range 25–365) days, there were 60 (71.4%) cumulative deaths in the low T3 syndrome group and 13 (48.1%) in the euthyroid group. Survival analysis showed a lower survival probability for patients with low FT3 than for those with normal FT3 (median OS, 60 vs. 365 days, p  = .011). In the multivariate analysis, low T3 syndrome was an independent prognostic factor for OS (HR = 2.474; 95% CI 1.351–4.532, p  = .003). Low T3 syndrome is frequently found and associated with worse outcomes in patients with sHLH.